Conflicts and Resiliency in Maya Angelou’s I know why the Caged Bird Sings - Michel Emmanuel Felix François (Entrelaces - Revista do Programa de Pós-Graduação em Letras-UFC, 2024)
Maia Angelou claims how she overcame her uncertainties and established her identity when she became an adult. As a young girl, she had to fight against the obstacles imposed by a rather sexist and racist society. It was not easy then to face institutionalized racism and survive in segregated America. When she was a child, she felt abandoned by her parents who sent her to Stamps to be raised by her paternal grandmother. While growing up in segregated South, she suffered from inferiority complex because of the color of her skin and her awkward body. She pictured herself waking up from a nightmare in which a beautiful white girl had been cursed by an evil fairy, jealous of her beauty, and transformed into a big black and awkward girl, with nappy hair and misaligned teeth. Angelou speaks of her alienation and displacement, not only in connection with the places where she lived but also with her own family. She testified the resentment of African Americans who were forced to live at the margin as they became an easy target of institutionalized racism and social inequalities. However, she also denounced the atmosphere of uncertainty she had to live with when the traumatic impact of a sexual assault left her with the most profound distrust of her own patriarchal community. All in all, Angelou’s biography explored her life experiences as a response to the unequal treatment of the black community within the American society Keywords Conflicts. Resistance. Prejudice.